High-density lead-free K0.5Bi0.5TiO3 ceramics: preparation, mechanical and dielectric properties. (3rd October 2018) - Czaja, P.; Suchanicz, J.; Bochenek, D.; Dercz, G.; Piasecki, M.; Hudy, W.
ABSTRACT: The preparation of high-density lead-free potassium-bismuth titanate K0.5 Bi0.5 TiO3 about 96–98% of the calculated density (X-ray), confirmed by the Archimedes method, is presented. All stages of the technological process are explained in detail. The control of microstructure was performed by scanning electron microscopy. The crystal structure and phase content of samples were determined by X-ray diffraction at each stage of sintering. Four types of samples were obtained under various technological conditions. The ultrasonic measurements of the obtained samples were carried out and basic parameters were determined, such as Young and Kirchoff modulus and Poisson's ratio were determined at room temperature. The dielectric measurements show that the maximum value of dielectric permittivity is shifted towards higher temperatures as the frequency increases. This feature is characteristic of ferroelectric relaxor materials. The presented materials can be a good starting point for the development of lead-free ceramics.